Paraneoplastic Limbic Encephalitis Resembling Acute Herpetic Encephalitis - Ioannis Markakis; Athanasios Papathanasiou; Ermioni Papageorgiou; Kostantinos Siarkos; Georgios Gkekas (Case Reports in Neurological Medicine)
Introduction. Paraneoplastic limbic encephalitis (PLE) is a rare disorder that typically follows a chronic or subacute course of personality changes, memory loss, seizures, and hallucinations. Early diagnosis is difficult and characteristic symptoms can be mimicked by a variety of conditions. We present a case of PLE, initially presenting as acute herpetic encephalitis. Case Presentation. A 56-year-old male was admitted for evaluation of acute onset headache, fever, and confusion. On neurological examination he was confused with MMSE score of 15/30. CSF analysis revealed marked lymphocytic pleocytosis. A possible diagnosis of acute herpetic encephalitis was rendered and patient was treated with acyclovir. CSF PCR was negative. Cranial MRI revealed bilateral hyperintense lesions in medial temporal lobes with contrast enhancement. Despite treatment with acyclovir patient was deteriorated; thus, a paraneoplastic syndrome was suspected. Chest CT showed a right paratracheal lymph node mass, while a biopsy revealed neuroendocrine lung cancer. Auto antibodies to Hu were also detected. The patient was treated with steroids and chemotherapy. Six months later, he had complete tumour remission and marked neurological improvement. Discussion. PLE can rarely invade acutely, being indistinguishable from herpetic encephalitis. Inclusion of PLE in the differential diagnosis of acute encephalitis is of great clinical significance.